Assessment of the bone quality of black female athletes using quantitative ultrasound - Laabes, E. P.; Vanderjagt, D. J.; Obadofin, M. O.; Sendeht, A. J.; Glew, R. H. (The Journal of Sports Medicine and Physical Fitness, 2008)
Aim: The mean daily calcium intake of adult Nigerians is reportedly low, and animal studies have shown that exercise-induced changes in the bones of growing mice are gender specific. We therefore sought to describe calcaneal broadband ultrasound attenuation (BUA), speed of sound (SOS), stiffness index (SI) and SI-based T-scores in a cohort of Nigerian female athletes; to assess the correlation of SI with energy expenditure; and to compare mean SI values between sports. Methods: We recruited 52 female athletes in 10 sporting categories, and recorded their anthropometric data. Activity levels were estimated using a questionnaire. Bone density was assessed using calcaneal ultrasound. Results: The mean age of athletes was 21±4 years (range 15-39 years). The mean body mass index (BMI) was 22.0±3.5 kg/m2, and was not different between the sub-group of footballers/runners (21.3±1.7 kg/m2) and other athletes (23.1±4.8 kg/m2, P=0.06). The mean energy expenditure was 32.2±9.5 kcal/kg/ day, and was not different between the sub-group of footballers/runners (30.8±9.2 kcal/kg/day) and other athletes (34.3±9.7 kcal/kg/day, P=0.19). The mean BUA of the athletes was 135±14 dB/MHz, the mean SOS was 1597±13 m/s, the mean SI was 118±15, and the median SI-based T-score was +1.1 (-I.6 to +3.53). The means of all ultrasound parameters were not significantly different between footballers/runners and other sportswomen. Conclusion: Consistent physical training may improve calcaneal SI of black females by one, and potentially by as much as three T-score units. Training intensity, rather than the qualitative aspects of a sport, appears to be a major determinant of SI in female Nigerian athletes.